Analisis Morfologi dan Kimia Akibat Cekaman Kromium pada Perkembangan Organ Floral, Gametofit dan Karakteristik Biji Selama Masa Generatif Tanaman Padi - Abel Rahmad Mulyono (Fakultas Pertanian, 2026)
Chromium (Cr) contamination is a limiting factor in rice production, particularly during the generative stage when reproductive development determines yield and seed quality. This study aimed to evaluate the effects of chromium stress on vegetative organs active during the generative phase, floral development, gametophyte performance, seed characteristics, and genetic stability of rice (Oryza sativa L. var. IR64). A Completely Randomized Design was applied with five chromium concentrations (0, 25, 50, 100, and 150 mg/L) and three replications. Observations included morphological traits, reproductive performance, seed biochemical contents, and DNA polymorphism analysis using RAPD markers. Results demonstrated that increasing chromium concentration reduced growth performance, impaired reproductive development, decreased seed quality and viability, and lowered amylose, protein, and lipid contents. Higher chromium levels also increased DNA polymorphism, indicating potential genomic instability. Chromium stress during the generative stage exhibits phytotoxic and potentially genotoxic effects on rice plants.
FINALISASI oleh Arif 2026 Juni 04
Keywords: chromium; generative stage; floral organs; seed viability; DNA polymorphism